The role of atopy in asthma development and persistence. Issue 2 (April 2020) - Di Cicco, Maria; D'Elios, Sofia; Peroni, Diego G.; Comberiati, Pasquale
Abstract : Purpose of review: Asthma is the most common chronic disease in pediatric age. Childhood-onset asthma, as opposed to adult-onset asthma, is typically characterized by a personal and often a family history of atopy and related markers of type 2-mediated inflammation. However, the interplay between atopy and asthma development is more complex than a linear dose–response relationship. Recent findings: Family and personal history of atopic diseases have been confirmed as major risk factors for asthma occurrence and persistence in children. Early life and multiple sensitizations to aeroallergens significantly increase the risk of asthma development in school age. Early life lower respiratory tract viral infections, especially caused by rhinovirus, also increase the susceptibility to atopic asthma in childhood. Human rhinovirus type C receptor CDHR3 polymorphisms have been shown to affect receptor epithelial expression, activation, and asthma development and exacerbation severity in children. Atopic sensitization and respiratory viral infections can synergistically enhance the susceptibility to asthma through multiple mechanisms, including the IgE-mediated inhibition of innate antiviral responses to rhinovirus. Emerging evidence shows that several nonatopic factors are also involved in the asthma pathogenesis in genetically predisposed individuals, including early life exposure to environmental factors, and lung and gut microbiome composition. Summary: The current review outlines recent data on the complex role of atopy in asthma pathogenesis and persistence, and addresses new research topics such as the role of epigenetics and the lung microbiome.